Association of Echinoderms with Seagrass on the South Coast of East Lombok - Sarwan Ardani; Abdul Syukur; Mohammad Liwa Ilhamdi (Jurnal Biologi Tropis, 2026)
Seagrass ecosystems have a vital function in sustaining the stability of coastal environments by enhancing biodiversity and maintaining key ecological processes of associated organisms, including Echinodermata. This study was conducted to examine the species composition, abundance, and distribution patterns of Echinodermata, to evaluate the composition and diversity of seagrass species, and to determine the degree of association between Echinodermata and seagrass in the southern coastal waters of East Lombok, specifically at Lungkak and Poton Bako Beaches. The research employed a survey method using a transect–quadrat technique in intertidal seagrass ecosystems, with subsequent analyses including the Shannon–Wiener diversity index, distribution pattern assessment, and Spearman correlation analysis to quantify the strength of the association. The study found that seagrass diversity indices at both sites were categorized as moderate, with relatively similar species composition, while Echinodermata communities were dominated by several key species exhibiting clustered to uniform distribution patterns. Correlation analysis indicated a positive to weak association between seagrass density and Echinodermata abundance. In conclusion, the seagrass beds in the study area continue to function as important habitats for Echinodermata, although signs of increasing environmental pressure were observed. These findings provide important scientific implications for seagrass ecosystem management and conservation-oriented regulation of coastal activities in East Lombok.